PENDAMPINGAN PADA KANTIN PESANTREN DALAM MENINGKATKAN PENDAPATAN USAHA MELALUI RENCANA PEMASARAN DAN PEMANFAATAN PENGGUNAAN PAMFLET - Riyanti, Riyanti; Aminah, Aidil; Rosliyati, Rosliyati; Warnida, Warnida (ABDINA: Jurnal Sosial dan Pengabdian kepada Masyarakat, 2023)
The purpose of this activity is to provide understanding, delivery and training to Central Canteen business partners in the aspects of marketing planning utilization of pamphlets so that they can increase their income. This mentoring activity is carried out by students Sharia Economics Study Program at the Dirosat Islamiyah Institute Prenduan Al-Amien Prenduan with a program that has four stages of implementation, namely preparation and planning, implementation, evaluation and monitoring. This stage ensures that program goals, targets and results are achieved. This activity is carried out using participatory methods such as observation, interviews, discussions focus groups, and joint decision making. The results of a series of 4 stages are an increase in Central Canteen TMI Al-Amien's revenue, an increase in the quantity and quality of Central Canteen TMI Al-Amien marketed, and an increase in the marketing of quality service products.